The Effect of the Interest Equalization Tax Act and the Interest Equalization Tax Extension Act on Purchases of Long-Term Bonds of Selected Countries Marketed in the United States: 1959 to March 1966 - Griffith, John R. (Journal of Finance, 1969)
John R. Griffith, Jr., The Effect of the Interest Equalization Tax Act and the Interest Equalization Tax Extension Act on Purchases of Long-Term Bonds of Selected Countries Marketed in the United States: 1959 to March 1966, The Journal of Finance, Vol. 24, No. 3 (Jun., 1969), pp. 538-539